Influences of Ruminococcus bromii and Peptostreptococcaceae on voluntary exercise behavior in a rodent model - Rusling, Matthew; Karim, Anisha; Kaye, Avi; Lee, Chia-Ming Jimmy; Wegman−Points, Lauren; Mathis, Victoria; Lampeter, Thomas; Yuan, Li-Lian (Frontiers in Microbiomes, 2024)
This study investigates the relationship between the gut microbiome and voluntary exercise, focusing on wheel running activity in a rat model. The gut microbiome plays a crucial role in host physiology, homeostasis, and behavior. Alterations in the gut microbiome have been linked to various pathological states and health conditions, including obesity. Given the strong association between physical inactivity and obesity development, our study aimed to identify microbiome factors associated with elevated levels of voluntary exercise.Male Sprague Dawley rats were used in the 4-week exercise paradigm in which voluntary wheel running behavior was monitored alongside weekly microbiome sampling from fecal pellets. We observed individual differences in running activity among the cohort. Significant positive correlations in running distance were identified across the 4-week time course, suggesting that running activity ranking was largely preserved. Furthermore, earlier running activity emerged as a potential predictor for subsequent running behaviors. Analysis of gut microbiome revealed that alpha diversity was positively correlated with daily running distances, with significant differences in beta diversity observed between high and low running groups. Taxonomic analysis showed distinct abundance differences between running and sedentary conditions, particularly in the Ruminococcaceae and Peptostreptococcaceae families.Our results suggest that the microbiome composition changes significantly early in exercise exposure, potentially influencing exercise behavior. Ruminococcaceae, particularly R. bromii, was identified as a significant contributor to exercise adaptation, while Peptostreptococcaceae was inversely related to running performance as well as alpha diversity. This study underscores the potential of the gut microbiome as a modulator of exercise behavior. Future research should focus on the biological mechanisms linking microbiome changes to exercise adaptation, with R. bromii and Peptostreptococcus as promising candidates for influencing exercise behaviors through future interventional studies.